Bacteriologic Profile and Antibiogram of Blood Culture Isolates in a Pediatric Care Unit - Prabhu, Kavitha; Bhat, Sevitha; Rao, Sunil (Journal of Laboratory Physicians, 2010)
Background / Aims: Septicemia is one of the important causes of mortality and morbidity in neonates and children. Blood culture is the gold standard for the diagnosis. Emergence of multidrug resistant bacterial strains is a major problem in the management of sepsis. Present study was undertaken to identify the common bacterial pathogens associated with pediatric sepsis and to determine their antibiotic susceptibility pattern.Materials and Methods: Blood cultures from 185 suspected cases of sepsis were examined. The growths from the subcultures were identified by conventional biochemical tests. Antibiotic susceptibility testing was performed by modified Kirby-Bauer disk diffusion method and drug resistant strains in primary screening were further processed for extended spectrum beta lactamases (ESBL) and methicillin resistant Staphylococcus aureus (MRSA) status by combination disk method (ESBL) and oxacillin disk diffusion method (MRSA).Results: Out of the 185 cultures obtained from suspected cases, 81 (44%) were culture positive. Fifty-two (35%) of the culture isolates were Gram negative bacilli. Twenty-eight (64%) of the isolates were Gram positive cocci. One case was of mixed infection. The prevalence of MRSA in 41 strains of S. aureus was found to be 29% (12 strains). The overall prevalence of ESBL producers among 28 Gram negative bacterial isolates was found to be 32% (9 strains).Conclusion: This study stresses the need for the continuous screening and surveillance for antibiotic resistance in pediatric care unit.
Keywords: Sepsis; methicillin resistant Staphylococcus aureus; extended spectrum beta lactamases; blood culture